Modern Luck Narratives of fortune in the long twentieth century - Gordon, Robert S.C (Comparative Literature and Culture, 2023)
Beliefs, superstitions and tales about luck are present across all human cultures, according to anthropologists. We are perennially fascinated by luck and by its association with happiness and danger, uncertainty and aspiration. Yet it remains an elusive, ungraspable idea, one that slips and slides over time: all cultures reimagine what luck is and how to tame it at different stages in their history, and the modernity of the 'long twentieth century' is no exception to the rule. Apparently overshadowed by more conceptually tight, scientific and characteristically modern notions such as chance, contingency, probability or randomness, luck nevertheless persists in all its messiness and vitality, used in our everyday language and the subject of studies by everyone from philosophers to psychologists, economists to self-help gurus. Modern Luck sets out to explore the enigma of luck's presence in modernity, examining the hybrid forms it has taken on in the modern imagination, and in particular in the field of modern stories. Indeed, it argues that modern luck is constituted through narrative, through modern luck stories. Analysing a rich and unusually eclectic range of narrative taken from literature, film, music, television and theatre - from Dostoevsky to Philip K. Dick, from Pinocchio to Cimino, from Curtiz to Kieślowski - it lays out first the usages and meanings of the language of luck, and then the key figures, patterns and motifs that govern the stories told about it, from the late nineteenth century to the present day.